From burnout to breakthrough: understanding the work-related stress-motivation Nexus in medical imaging professionals - Alo Edin; Hikma Ali; Yenuse Molla; Miesa Gelchu; Ali Beyene; Angefa Ayele (Frontiers Media S.A., 2024)
BackgroundWork-related stress is a pervasive issue in the global occupational health landscape, ranking as the second-most common problem after low back pain. In Ethiopia, the healthcare sector is particularly affected by low staff motivation and stressed workers, which can significantly impact the functioning of health systems. However, when it comes to medical imaging professionals (MIPs), there is a lack of substantial evidence regarding the relationship between work-related stress and motivation. Therefore, this study aimed to address this gap by assessing the connection between work-related stress and motivation among medical imaging professionals in the study area.Materials and methodsTo assess the relationship between work-related stress and motivation among medical imaging professionals in Addis Ababa, a facility-based cross-sectional study was conducted. The study included a sample of 420 medical imaging professionals, who were randomly selected using a simple random sampling technique. The data collected from the participants were entered into Epi Data 3.1 and analyzed using STATA 14.2. Bivariable and multivariable analyses were performed to explore the associations between work-related stress and motivation, taking into account various factors. To determine statistical significance, a p-value of less than 0.05 was used as the threshold.ResultsThis study found that 57.4% of the participants experienced workplace stress and 46.4% reported being motivated. We observed a negative relationship between work-related stress and job motivation. The findings indicated that sex (adjusted odds ratio (AOR) = 1.819, 95% confidence interval (CI): 1.125, 2.94), age (AOR = 0.186, 95% CI: 0.04, 0.78), radiation (AOR = 2.21, 95% CI: 1.377, 3.57), leadership (AOR = 2.54, 95% CI: 1.475, 4.385), financial incentives (AOR = 1.78, 95% CI: 1.052, 3.022), and profession category (AOR = 2.57, 95% CI: 1.006, 6.561) were significantly associated with workplace stress. In addition, profession category (AOR = 0.22, 95% CI: 0.78, 0.63), smoking (AOR = 0.262, 95% CI: 0.08, 0.77), permanent workplace (AOR = 4.321, 95% CI: 1.988, 9.39), monthly income (AOR = 4.589, 95% CI: 1.37, 15.288), and financial incentives (AOR = 3.39, CI: 2.093, 5.51) were significantly associated with job motivation.ConclusionBased on the results of the current study, it can be inferred that work-related stress is substantial, whereas job motivation is lacking among medical imaging professionals. The study found that several factors, including sex, age, radiation, leadership, financial incentives, and profession category, were significantly associated with workplace stress. In addition, factors such as profession, smoking, permanent workplace, monthly income, and financial incentives were found to be significantly associated with job motivation. Notably, a negative relationship was observed between work-related stress and motivation.